Toner binder manufacturing method
Patent Information
- Application Number
- JP2021028891
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-03
- Filing Date
- 2021-02-25
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-02-25
AI Technical Summary
【0013】 本発明により、低温定着性、耐ホットオフセット性を維持しつつ、画像強度、耐熱保存性、耐水性、帯電維持率、耐久性及び臭気に優れたトナーバインダーを提供することが可能になる。また、ポリエステル樹脂(A1)とエポキシ化合物(E)との反応時間の短縮が可能になり、トナーバインダーの製造性に優れる。
Smart Images

Figure 0007638730000001 
Figure 0007638730000002 
Figure 0007638730000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a toner binder. [Background technology]
[0002] 2. Description of the Related Art In recent years, with the development of electrophotographic systems, the demand for electrophotographic apparatuses such as copying machines and laser printers has increased rapidly, and the requirements for their performance have also become more sophisticated.
[0003] Conventionally, for full-color electrophotography, a method and apparatus have been known in which a latent image based on color image information is formed on a latent image carrier such as an electrophotographic photosensitive member, the latent image is developed with a toner of a corresponding color, and then the toner image is transferred onto a transfer material. After repeating such image forming steps, the toner image on the transfer material is heated and fixed to obtain a multi-color image. To pass through these processes without any problems, the toner must first maintain a stable charge, and then must have good fixability to paper. In addition, the toner must not block in the device because the fixing section of the device has a heater, causing the temperature to rise inside the device.
[0004] Furthermore, in order to promote miniaturization, speedup, and image quality improvement of electrophotographic apparatuses, as well as to save energy by reducing the energy consumption in the fixing process, there is a strong demand for improving the low-temperature fixing property of toner. Recently, many kinds of paper are used as transfer materials, such as recycled paper with large surface irregularities and coated paper with a smooth surface. To deal with the surface properties of these transfer materials, a fixing device with a wide nip width, such as a soft roller or a belt roller, is preferably used. However, when the nip width is widened, the contact area between the toner and the fixing roller increases, and the melted toner adheres to the fixing roller, which is called a high-temperature offset phenomenon, occurs, so hot offset resistance is required.
[0005] The toner binder has a significant effect on the toner characteristics as described above. Known examples of the toner binder include polystyrene resin, styrene-acrylic resin, polyester resin, epoxy resin, polyurethane resin, and polyamide resin. Recently, polyester resin has been attracting particular attention because it is easy to balance heat-resistant storage stability and fixing ability.
[0006] As a method for expanding the fixing temperature range, a toner using a polyester resin containing an unsaturated carboxylic acid as a constituent component has been proposed (Patent Document 1). Also, a polyester-vinyl composite resin in which a polyester resin containing an unsaturated carboxylic acid as a constituent component is combined with a vinyl resin has been proposed (Patent Documents 2 and 3). However, although these methods can prevent the offset phenomenon at high temperatures to some extent, the minimum fixing temperature is insufficient, and the demand for high speed and energy saving is not yet fully met. In addition, blocking occurs due to water absorption under high temperature and high humidity, so the water resistance is insufficient.
[0007] On the other hand, a toner using a crystalline vinyl resin as a material for lowering the minimum fixing temperature has been proposed (Patent Documents 4 and 5). Although this method improves the low-temperature fixing property, the hot offset resistance at high temperatures is insufficient.
[0008] As a method for improving the minimum fixing temperature while maintaining hot offset resistance, a toner binder has been proposed in which a long-chain alkyl acrylate is polymerized to lower the melt viscosity and a polyester resin containing an unsaturated carboxylic acid as a constituent component is combined (Patent Document 6). However, with this method, decomposition products such as initiators generated when crosslinking the unsaturated carboxylic acid remain, causing odors and insufficient charge retention rate under high temperature and high humidity conditions.
[0009] As described above, there has not been an excellent toner binder that satisfies all of the requirements for image strength, heat-resistant storage stability, water resistance, charge retention rate, durability, and odor while maintaining low-temperature fixing property and hot offset resistance. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2017-003985 A [Patent Document 2] JP 2015-135485 A [Patent Document 3] JP 2018-054888 A [Patent Document 4] JP 2007-193069 A [Patent Document 5] International Publication No. 2018 / 110593 [Patent Document 6] International Publication No. 2019 / 073731 Summary of the Invention [Problem to be solved by the invention]
[0011] An object of the present invention is to provide a toner binder which satisfies all of the requirements for image strength, heat-resistant storage stability, water resistance, charge retention rate, durability and odor while maintaining low-temperature fixing property and hot offset resistance. [Means for solving the problem]
[0012] The present inventors have conducted extensive research and have arrived at the present invention. That is, the present invention relates to a resin (B) having an acid value of less than 1 mgKOH / g and catalyst A method for producing a toner binder, comprising the step of reacting a polyester resin (A1) having an acid value of 1 mgKOH / g or more with an epoxy compound (E) in the presence of (F), The resin (B) is a polyester resin (B1) and / or a vinyl resin (B2), the vinyl resin (B2) is a crystalline vinyl resin which is a polymer having, as a constituent monomer, a monomer (a) which is a (meth)acrylate having a chain hydrocarbon group and having 21 to 40 carbon atoms and / or a vinyl ester having a chain hydrocarbon group and having 21 to 40 carbon atoms, The method for producing a toner binder, wherein (F) is a compound represented by the following general formula (1), [ka] [In general formula (1), R 1 ~R 3 are each independently a hydrogen atom, an alkyl group, or an aryl group. Effect of the Invention
[0013] The present invention makes it possible to provide a toner binder that is excellent in image strength, heat-resistant storage stability, water resistance, charge retention rate, durability, and odor while maintaining low-temperature fixing property and hot offset resistance. In addition, the reaction time between the polyester resin (A1) and the epoxy compound (E) can be shortened, and the toner binder is excellent in manufacturability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The method for producing a toner binder of the present invention comprises the steps of: catalyst The method includes a step of reacting a polyester resin (A1) having an acid value of 1 mgKOH / g or more with an epoxy compound (E) in the presence of (F). Since the polyester resin (A1) and the epoxy compound (E) are reacted in the presence of the resin (B), the reaction product of the polyester resin (A1) and the resin (B) which generally have differences in viscosity and composition and cannot be mixed uniformly can be made into a uniform mixture, and a toner binder having a wide range of fixing temperatures can be obtained. catalyst Since the polyester resin (A1) is reacted with the epoxy compound (E) in the presence of (F), the reaction time is shortened and side reactions such as an ester exchange reaction between the reaction product of the polyester resin (A1) and the resin (B) can be reduced, and the functional separation of low temperature fixing property and hot offset resistance is less hindered.
[0015] The polyester resin (A1) in the present invention is a polyester resin obtained by polycondensation of an alcohol component (x) and a carboxylic acid component (y), and the composition of the resin is not particularly limited as long as it has an acid value of 1 mgKOH / g or more and reacts with an epoxy compound (E). The polyester resin (A1) may be a single type, or a combination of two or more types.
[0016] The polyester resin (A1) is a resin obtained by polycondensation of an alcohol component (x) and a carboxylic acid component (y).
[0017] The alcohol component (x) of the polyester resin (A1) includes a diol (x1) and a trihydric or higher polyol (x2). These may be used alone or in combination of two or more.
[0018] Examples of the diol (x1) include alkylene glycols having 2 to 36 carbon atoms (ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol), alkylene ether glycols having 4 to 36 carbon atoms (diethylene glycol, triethylene glycol, etc.), Examples of suitable alkylene diols include alicyclic diols having 6 to 36 carbon atoms (1,4-cyclohexanedimethanol, hydrogenated bisphenol A, etc.), (poly)alkylene oxide adducts of the above-mentioned alicyclic diols (preferably having an average number of moles added of 1 to 30), aromatic diols [monocyclic dihydric phenols (e.g., hydroquinone, etc.) and bisphenols, etc.] and alkylene oxide adducts of the above-mentioned aromatic diols (preferably having an average number of moles added of 2 to 30).
[0019] The alkylene oxide adducts of the bisphenols are obtained by adding alkylene oxide (hereinafter, "alkylene oxide" may be abbreviated as AO) to the bisphenols.
[0020] The bisphenols include those represented by the following general formula (2). HO-Ar-P-Ar-OH (2) [In the formula, P represents an alkylene group having 1 to 3 carbon atoms; 2represents -, -O-, -S- or a direct bond, and Ar represents a phenylene group in which a hydrogen atom may be substituted with a halogen atom or an alkyl group having 1 to 30 carbon atoms.]
[0021] Specific examples of bisphenols include bisphenol A, bisphenol F, bisphenol B, bisphenol AD, bisphenol S, trichlorobisphenol A, tetrachlorobisphenol A, dibromobisphenol F, 2-methylbisphenol A, 2,6-dimethylbisphenol A, and 2,2'-diethylbisphenol F, and two or more of these can be used in combination.
[0022] Examples of the alkylene oxide to be added to the bisphenols include alkylene oxides having 2 to 30 carbon atoms, such as ethylene oxide (hereinafter, "ethylene oxide" may be abbreviated as EO), 1,2- or 1,3-propylene oxide (hereinafter, "1,2-propylene oxide" may be abbreviated as PO), 1,2-, 2,3-, 1,3- or iso-butylene oxide, tetrahydrofuran, and combinations of two or more of these.
[0023] Examples of the tri- or higher hydric polyol (x2) include aliphatic polyhydric alcohols having 3 to 36 carbon atoms and a valence of tri- or higher, sugars and derivatives thereof, AO adducts of aliphatic polyhydric alcohols (average number of moles added is preferably 1 to 30), AO adducts of trisphenols (trisphenol PA, etc.) (average number of moles added is preferably 2 to 30), and AO adducts of novolak resins (including phenol novolak and cresol novolak, etc., having an average degree of polymerization of preferably 3 to 60) (average number of moles added is preferably 2 to 30).
[0024] Examples of the aliphatic polyhydric alcohol having 3 to 36 carbon atoms and a valence of three or more include alkane polyols and their intramolecular or intermolecular dehydration products, such as glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, sorbitan, polyglycerin, and dipentaerythritol. Furthermore, examples of sugars and their derivatives include sucrose and methyl glucoside.
[0025] Of these alcohol components (x), from the viewpoint of dispersibility, diols (x1) are preferred, alkylene oxide adducts of aromatic diols are more preferred, alkylene oxide adducts of bisphenols (average number of moles added is preferably 2 to 5) are further preferred, alkylene oxide adducts of bisphenol A (average number of moles added is preferably 2 to 5) are particularly preferred, and EO and / or PO adducts of bisphenol A (average number of moles added is preferably 2 to 3) are most preferred.
[0026] The diol (x1) in the alcohol component (x) of the polyester resin (A1) is preferably 80 to 100 mol %. When the diol (x1) and the trihydric or higher polyol (x2) are used in combination, the molar ratio of the diol (x1) to the trihydric or higher polyol (x2) [(x1) / (x2)] is preferably 99 / 1 to 80 / 20, more preferably 98 / 2 to 85 / 15, from the viewpoint of the charge retention rate (charge retention rate under high temperature and high humidity conditions).
[0027] Furthermore, the alcohol component of the polyester resin (A1) may contain a mono-ol component in addition to the alcohol component (x) as necessary. Examples of the mono-ol include linear or branched alkyl alcohols having 1 to 30 carbon atoms (methanol, ethanol, isopropanol, 1-decanol, dodecyl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, behenyl alcohol, lignoceryl alcohol, etc.).
[0028] The carboxylic acid component (y) of the polyester resin (A1) may be a dicarboxylic acid (y1) or a trivalent or higher polycarboxylic acid (y2). These may be used alone or in combination of two or more.
[0029] Examples of the dicarboxylic acid (y1) include aromatic dicarboxylic acids having 8 to 36 carbon atoms (phthalic acid, isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, etc.), aliphatic dicarboxylic acids having 2 to 50 carbon atoms (oxalic acid, malonic acid, succinic acid, adipic acid, oleaginic acid, sebacic acid, etc.), alicyclic dicarboxylic acids having 6 to 40 carbon atoms [dimer acids (dimerized linoleic acid, etc.)], alkene dicarboxylic acids having 4 to 36 carbon atoms (alkenyl succinic acids such as dodecenyl succinic acid, maleic acid, fumaric acid, citraconic acid, mesaconic acid, etc.), and ester-forming derivatives thereof. Here, the ester-forming derivative means carboxylic acid anhydride, alkyl (methyl, ethyl, butyl, stearyl, etc. having 1 to 24 carbon atoms, preferably those having 1 to 4 carbon atoms) esters, and partial alkyl esters.
[0030] Examples of the trivalent or higher polycarboxylic acid (y2) include trivalent or higher aromatic polycarboxylic acids having 9 to 20 carbon atoms (such as trimellitic acid and pyromellitic acid), aliphatic (including alicyclic) tricarboxylic acids having 6 to 36 carbon atoms (such as hexanetricarboxylic acid and decanetricarboxylic acid), and ester-forming derivatives thereof.
[0031] Among these carboxylic acid components (y), from the viewpoint of charge retention rate (charge retention rate under high temperature and high humidity conditions), aromatic dicarboxylic acids having 8 to 36 carbon atoms, aliphatic dicarboxylic acids having 2 to 50 carbon atoms, aromatic polycarboxylic acids having 9 to 20 carbon atoms, and alkene dicarboxylic acids having 4 to 36 carbon atoms are preferred, terephthalic acid, isophthalic acid, adipic acid, succinic acid, maleic acid, fumaric acid, trimellitic acid, and pyromellitic acid are more preferred, and terephthalic acid, isophthalic acid, adipic acid, and trimellitic acid are even more preferred. In addition, anhydrides and lower alkyl esters of these acids may be used.
[0032] The dicarboxylic acid (y1) in the carboxylic acid component (y) of the polyester resin (A1) is preferably 60 to 100 mol %. When the dicarboxylic acid (y1) and the trivalent or higher polycarboxylic acid (y2) are used in combination, the molar ratio [(y1) / (y2)] of the dicarboxylic acid (y1) to the trivalent or higher polycarboxylic acid (y2) is preferably 99 / 1 to 65 / 35, more preferably 98 / 2 to 69 / 31, from the viewpoint of the charge retention rate (charge retention rate under high temperature and high humidity conditions).
[0033] Furthermore, as the carboxylic acid component of the polyester resin (A1), a monocarboxylic acid component may be contained as necessary in addition to the carboxylic acid component (y). Examples of the monocarboxylic acid include aromatic monocarboxylic acids having 7 to 37 carbon atoms (benzoic acid, toluic acid, 4-ethylbenzoic acid, 4-propylbenzoic acid, etc.), and aliphatic (including alicyclic) monocarboxylic acids having 2 to 50 carbon atoms (acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, lauric acid, myristic acid, palmitic acid, margaric acid, stearic acid, behenic acid, etc.).
[0034] The polyester resin (A1) in the present invention can be produced in the same manner as known polyester resin production methods. For example, the polycondensation reaction can be carried out by polycondensing the alcohol component (x) and the carboxylic acid component (y) in an inert gas (nitrogen gas, etc.) atmosphere at a reaction temperature of preferably 150 to 280°C, more preferably 160 to 250°C, and even more preferably 170 to 235°C. The reaction time is preferably 30 minutes or more, more preferably 2 to 40 hours, from the viewpoint of ensuring the polycondensation reaction. It is also effective to reduce the pressure in order to improve the reaction rate at the end of the reaction.
[0035] In this case, an esterification catalyst can be used as necessary. Examples of the esterification catalyst include tin-containing catalysts (e.g., dibutyltin oxide, etc.), antimony trioxide, titanium-containing catalysts [e.g., titanium alkoxide, potassium oxalate titanate, titanium terephthalate, titanium alkoxide terephthalate, catalysts described in JP-A-2006-243715 {titanium diisopropoxybis(triethanolaminate), titanium dihydroxybis(triethanolaminate), titanium monohydroxytris(triethanolaminate), titanyl bis(triethanolaminate) and their intramolecular polycondensates, etc.} and catalysts described in JP-A-2007-11307 (titanium tributoxyterephthalate, titanium triisopropoxyterephthalate, titanium diisopropoxyditerephthalate, etc.)], zirconium-containing catalysts (e.g., zirconyl acetate, etc.), and zinc acetate, etc. Among these, titanium-containing catalysts are preferred.
[0036] In order to stably proceed with the polymerization of the polyester, a stabilizer may be added, such as hydroquinone, methylhydroquinone, 4-tert-butylcatechol, 4-methoxyphenol, 2-tert-butyl-4-methoxyphenol, 2,6-di-tert-butyl-4-methoxyphenol, and a hindered phenol compound.
[0037] The weight ratio of the alcohol component (x) and the carboxylic acid component (y) used in the polycondensation reaction is, in terms of the equivalent ratio of hydroxyl groups to carboxyl groups ([OH] / [COOH]), preferably 1 / 2 to 2 / 1, more preferably 1 / 1.5 to 1.5 / 1, and even more preferably 1 / 1.3 to 1.3 / 1. The hydroxyl groups are those derived from the alcohol component (x), and the carboxyl groups are the sum of the carboxyl groups derived from the carboxylic acid component (y).
[0038] The polyester resin (A1) may or may not have crystallinity, but is preferably an amorphous polyester resin from the viewpoint of heat-resistant storage stability. The amorphous polyester resin can be obtained by increasing the content of a branched monomer, for example, an alkylene oxide adduct of a bisphenol, in the alcohol component (x) and the carboxylic acid component (y) used.
[0039] The polyester resin (A1) may be any of a linear polyester resin, a crosslinked polyester resin, or a mixture of a linear polyester resin and a crosslinked polyester resin, but from the viewpoint of charge retention, it is preferably a crosslinked polyester resin or a mixture of a linear polyester resin and a crosslinked polyester resin, and more preferably a crosslinked polyester resin. The crosslinked polyester resin can be produced by using a trivalent or higher polyol (x2) and / or a trivalent or higher polycarboxylic acid (y2) as the alcohol component (x) and the carboxylic acid component (y) of the polyester resin (A1).
[0040] Glass transition temperature (Tg A1 From the viewpoints of low-temperature fixability, heat-resistant storage stability, water resistance and durability, the temperature is preferably from -35 to 55°C, more preferably from -15 to 55°C, further preferably from 15 to 55°C, and particularly preferably from 35 to 55°C. The Tg is measured using a differential scanning calorimeter (DSC) according to the method (DSC method) specified in ASTM D3418-82.
[0041] The peak top molecular weight (hereinafter sometimes abbreviated as Mp) of the polyester resin (A1) is preferably from 2,000 to 200,000, more preferably from 2,500 to 100,000, further preferably from 3,000 to 60,000, and particularly preferably from 5,000 to 30,000, from the viewpoints of low-temperature fixability and heat-resistant storage stability. The Mp of the polyester resin (A1) is measured by gel permeation chromatography (GPC) under the following conditions.
[0042] First, a calibration curve is prepared by gel permeation chromatography (GPC) using standard polystyrene samples. Next, the sample is separated by GPC, and the count number of the separated sample at each retention time is measured. Next, a chart of the molecular weight distribution of the sample is prepared from the logarithmic value of the calibration curve and the obtained count number. The maximum value of the peak in the chart of the molecular weight distribution is the peak top molecular weight Mp. When there are multiple peaks in the molecular weight distribution chart, the maximum value among those peaks is taken as the peak top molecular weight (Mp). The measurement conditions for GPC measurement are as follows:
[0043] In the present invention, the peak top molecular weight Mp, number average molecular weight (hereinafter sometimes abbreviated as Mn), and weight average molecular weight (hereinafter sometimes abbreviated as Mw) of the polyester resin (A1) can be measured using GPC under the following conditions. Equipment: HLC-8120 [Tosoh Corporation] Column: 2 TSK GEL GMH6 [Tosoh Corporation] Measurement temperature: 40℃ Sample solution: 0.25% by weight in THF Solution injection volume: 100μL Detector: Refractive index detector Reference material: 12 standard polystyrenes (TSKstandard POLYSTYRENE) (molecular weights: 500, 1,050, 2,800, 5,970, 9,100, 18,100, 37,900, 96,400, 190,000, 355,000, 1,090,000, 2,890,000) [manufactured by Tosoh Corporation] For measuring the molecular weight, a sample is dissolved in tetrahydrofuran (THF) to a concentration of 0.25% by weight, and the insoluble matter is filtered off using a glass filter to obtain a sample solution. Incidentally, for the resin (B) and toner binder described later, Mp, Mn and Mw can be determined in the same manner as above.
[0044] The polyester resin (A1) is a polyester resin having an acid value of 1 mgKOH / g or more. An acid value of 1 mgKOH / g or more means that the polyester resin (A1) has a carboxyl group or the like necessary for reacting with the epoxy compound (E). From the viewpoints of water resistance, hot offset resistance, heat resistant storage stability and charge retention, the acid value of the polyester resin (A1) is preferably 7.0 to 50.0 mgKOH / g, more preferably 10.0 to 49.0 mgKOH / g, and even more preferably 20.0 to 49.0 mgKOH / g.
[0045] The acid value of the polyester resin (A1) can be measured under the following conditions by the method specified in JIS K0070. 1) Accurately weigh the sample and let its weight be S (g). 2) Place the sample in a 200mL Erlenmeyer flask, add 50mL of a mixed solvent of acetone, methanol, and toluene (acetone:methanol:toluene = 12.5:12.5:75), add a few drops of phenolphthalein indicator, and titrate with 0.1N KOH-methanol solution. The amount of KOH solution used at this time is A (ml). At the same time, perform a blank test, and the amount of KOH solution used at this time is B (ml). 3) Calculate the acid value using the following formula. Acid value = (AB) × f × 5.61 ÷ S (f: titer of KOH solution) The acid values of the resin (B) and the toner binder described below can also be determined in the same manner as above.
[0046] The epoxy compound (E) is not particularly limited as long as it has an epoxy group in the molecule, but from the viewpoint of charge retention rate (charge retention rate under high temperature and high humidity), a polyfunctional epoxy compound having two or more epoxy groups in the molecule is preferred. Examples of the polyfunctional epoxy compound include aromatic polyepoxy compounds, heterocyclic polyepoxy compounds, alicyclic polyepoxy compounds, and aliphatic polyepoxy compounds. The epoxy compound (E) may be used alone or in combination of two or more.
[0047] Examples of the aromatic polyepoxy compounds include glycidyl ethers of polyhydric phenols, glycidyl esters of aromatic polycarboxylic acids, glycidyl aromatic polyamines, and other aromatic polyepoxy compounds.
[0048] Glycidyl ethers of polyhydric phenols include bisphenol F diglycidyl ether, bisphenol A diglycidyl ether, bisphenol B diglycidyl ether, bisphenol AD diglycidyl ether, bisphenol S diglycidyl ether, halogenated bisphenol A diglycidyl ether, tetrachloro bisphenol A diglycidyl ether, catechin diglycidyl ether, resorcinol diglycidyl ether, hydroquinone diglycidyl ether, pyrogallol triglycidyl ether, 1,5-dihydroxynaphthalene diglycidyl ether, dihydroxybiphenyl diglycidyl ether, octachloro-4,4'-dihydroxybiphenyl diglycidyl ether, tetramethylbiphenyl diglycidyl ether, dihydroxynaphthyl cresol triglycidyl ether, tris(hydroxyphenyl)methane triglycidyl ether, dinaphthyltriol triglycidyl ether, and tetrakis(4-hydroxyphenyl)ethane tetraglycidyl ether. ter, p-glycidylphenyldimethyltriyl bisphenol A glycidyl ether, trismethyl-t-butyl-butylhydroxymethane triglycidyl ether, 9,9'-bis(4-hydroxyphenyl)fluoroenyl glycidyl ether, 4,4'-oxybis(1,4-phenylethyl)tetracresol glycidyl ether, 4,4'-oxybis(1,4-phenylethyl)phenyl glycidyl ether, bis(dihydroxynaphthalene) tetraglycidyl ether, novolac type epoxy resins (phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, limonene phenol novolac type epoxy resins, etc.), bisphenol A type epoxy resins, polyglycidyl ethers of polyphenols obtained by the condensation reaction of polyhydric phenols with glyoxal, glutaraldehyde or formaldehyde, and polyglycidyl ethers of polyphenols obtained by the condensation reaction of resorcinol with acetone.
[0049] Examples of the glycidyl ester of an aromatic polycarboxylic acid include diglycidyl phthalate, diglycidyl isophthalate, and diglycidyl terephthalate.
[0050] Examples of the glycidyl aromatic polyamines include N,N-diglycidylaniline, N,N,N',N'-tetraglycidylxylylenediamine, and N,N,N',N'-tetraglycidyldiphenylmethanediamine.
[0051] Other aromatic polyepoxy compounds include triglycidyl ethers of p-aminophenol, diglycidyl urethane compounds obtained by the addition reaction of tolylene diisocyanate or diphenylmethane diisocyanate with glycidol, glycidyl group-containing polyurethane (pre)polymers obtained by reacting the above two reactants with a polyol, and diglycidyl ethers of AO adducts of bisphenol A.
[0052] An example of the heterocyclic polyepoxy compound is trisglycidylmelamine.
[0053] Examples of the alicyclic polyepoxy compounds include vinylcyclohexene dioxide, limonene dioxide, dicyclopentadiene dioxide, bis(2,3-epoxycyclopentyl)ether, ethylene glycol bisepoxydicyclopentylether, 3,4-epoxycyclohexylmethyl-3',4'-epoxycyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-3',4'-epoxy-6'-methylcyclohexanecarboxylate, bis(3,4-epoxy-6-methylcyclohexylmethyl)adipate, bis(3,4-epoxy-6-methylcyclohexylmethyl)butylamine, 1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol, and dimer acid diglycidyl ester. Examples of the alicyclic polyepoxy compounds include hydrogenated products of the aromatic polyepoxy compounds.
[0054] Examples of the aliphatic polyepoxy compound include polyglycidyl ethers of aliphatic polyhydric alcohols, polyglycidyl esters of aliphatic polycarboxylic acids, and glycidyl aliphatic amines.
[0055] Examples of polyglycidyl ethers of aliphatic polyhydric alcohols include ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tetramethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polytetramethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, sorbitol polyglycidyl ether, and polyglycerol polyglycidyl ether.
[0056] Examples of the polyglycidyl ester of an aliphatic polycarboxylic acid include diglycidyl oxalate, diglycidyl malate, diglycidyl succinate, diglycidyl glutarate, diglycidyl adipate, and diglycidyl pimelate.
[0057] Examples of glycidyl aliphatic amines include N,N,N',N'-tetraglycidylhexamethylenediamine. The aliphatic polyepoxy compounds also include (co)polymers of diglycidyl ether and glycidyl (meth)acrylate.
[0058] Among these polyfunctional epoxy compounds, from the viewpoint of durability and charge retention rate (charge retention rate under high temperature and high humidity), aromatic polyepoxy compounds, alicyclic polyepoxy compounds, and aliphatic polyepoxy compounds are preferred, aromatic polyepoxy compounds are more preferred, and novolac epoxy resins and bisphenol A epoxy resins are even more preferred. The above-mentioned epoxy compounds (E) may be used alone or in combination of two or more kinds.
[0059] The epoxy compound (E) in the present invention is preferably a polyfunctional epoxy compound having an epoxy equivalent of 170 to 900 (g / eq, the same applies below), more preferably 180 to 900, and even more preferably 190 to 900. When the epoxy equivalent of the epoxy compound (E) is 170 or more, low-temperature fixing property is good, and when it is 900 or less, the charge retention rate (charge retention rate under high temperature and high humidity conditions) is good.
[0060] The weight ratio of the polyester resin (A1) to the epoxy compound (E) [(A1):(E)] is from the viewpoints of dispersibility and charge retention rate (charge retention rate under high temperature and high humidity conditions) of 65:35 to 98:2, preferably 67:33 to 98:2 wt%, and more preferably 68:32 to 98:2 wt%.
[0061] In the present invention, the reaction product of the polyester resin (A1) and the epoxy compound (E) is a resin (B) and catalyst It can be obtained by reacting polyester resin (A1) with epoxy compound (E) in the presence of (F). From the viewpoint of hot offset resistance, the above reaction product is preferably a crosslinked resin, and it can be obtained by using the above multifunctional epoxy compound having an epoxy equivalent of 170 to 900 as the epoxy compound (E). The reaction is preferably carried out in an inert gas (nitrogen gas, etc.) atmosphere. From the viewpoint of ensuring the reaction, the reaction temperature is preferably 100 to 200° C., more preferably 130 to 190° C., and even more preferably 150 to 180° C. The reaction time is preferably 1 to 180 minutes, more preferably 2 to 18 minutes, from the viewpoints of low-temperature fixability, hot offset resistance, and odor.
[0062] The manufacturing method of the present invention comprises the steps of: catalyst The method also includes a step of reacting the polyester resin (A1) with the epoxy compound (E) in the presence of (F). catalyst (F) is a compound represented by general formula (1), and may be one type alone or two or more types in combination. [ka] In the above general formula (1), R 1 ~R 3 are each independently a hydrogen atom, an alkyl group, or an aryl group, and examples of the alkyl group include alkyl groups having 1 to 4 carbon atoms (such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, and a tert-butyl group), and examples of the aryl group include aryl groups having 6 to 10 carbon atoms (such as a phenyl group, a benzyl group, a tolyl group, and a xylyl group). In general formula (1), R 1 ~R 3 From the viewpoints of image strength, durability, water resistance and manufacturability, is preferably hydrogen, an alkyl group having 1 to 4 carbon atoms and an aryl group having 6 to 10 carbon atoms, and more preferably hydrogen, a methyl group, an ethyl group and a phenyl group.
[0063] Satisfying the above general formula (1) catalyst Specific examples of (F) include imidazole, 2-methylimidazole, 4-methylimidazole, 2-ethylimidazole, 2-propylimidazole, 2-phenylimidazole, 2,4-methylimidazole, 2-ethyl-4-methylimidazole, and 2,4,5-triphenylimidazole.
[0064] The reaction of the polyester resin (A1) with the epoxy compound (E) may be carried out using any other known reaction system other than those mentioned above. catalyst (Tertiary amines, imidazoles, quaternary ammonium salts, etc.) can also be added.
[0065] The production method of the present invention includes a step of reacting a polyester resin (A1) with an epoxy compound (E) in the presence of a resin (B).
[0066] Resin (B) is not particularly limited in composition as long as it has an acid value of less than 1 mgKOH / g, and examples thereof include polyester resin (B1), vinyl resin (B2), polyurethane resin (B3), epoxy resin (B4), polyamide resin (B5), etc., and may be used alone or in combination of two or more. Among the above resins, polyester resin (B1) and vinyl resin (B2) are preferred from the viewpoint of low-temperature fixing property. In addition, the acid value of resin (B) is preferably 0.3 mgKOH / g or less, more preferably 0 mgKOH / g.
[0067] The polyester resin (B1) is a polyester resin obtained by polycondensation of an alcohol component (x) and a carboxylic acid component (y), and is not particularly limited as long as the acid value is less than 1 mgKOH / g.
[0068] The alcohol component (x) of the polyester resin (B1) may be the same as that of the polyester resin (A1).
[0069] Of the above alcohol components (x), from the viewpoint of low-temperature fixability, diols (x1) are preferred, alkylene oxide adducts of aromatic diols are more preferred, alkylene oxide adducts of bisphenols (average number of moles added is preferably 2 to 5) are further preferred, alkylene oxide adducts of bisphenol A (average number of moles added is preferably 2 to 5) are particularly preferred, and EO and / or PO adducts of bisphenol A (average number of moles added is preferably 2 to 3) are most preferred.
[0070] The carboxylic acid component (y) of the polyester resin (B1) may be the same as that of the polyester resin (A1).
[0071] Among the carboxylic acid components (y), from the viewpoint of charge retention rate (charge retention rate under high temperature and high humidity conditions), aromatic dicarboxylic acids having 8 to 36 carbon atoms, aliphatic dicarboxylic acids having 2 to 50 carbon atoms, and aromatic polycarboxylic acids having 9 to 20 carbon atoms are preferred, aromatic dicarboxylic acids having 8 to 36 carbon atoms, and aliphatic dicarboxylic acids having 2 to 50 carbon atoms are more preferred, and terephthalic acid, isophthalic acid, adipic acid, succinic acid, maleic acid, and fumaric acid are even more preferred. Furthermore, anhydrides and lower alkyl esters of these acids may be used.
[0072] The weight ratio of the alcohol component (x) and the carboxylic acid component (y) used in the polycondensation reaction is preferably 1 / 1 to 2 / 1, more preferably 1 / 1 to 1.5 / 1, and even more preferably 1.05 / 1 to 1.3 / 1, as the equivalent ratio of hydroxyl groups to carboxyl groups ([OH] / [COOH]). The hydroxyl groups are those derived from the alcohol component (x), and the carboxyl groups are the sum of the carboxyl groups derived from the carboxylic acid component (y).
[0073] The polyester resin (B1) in the present invention can be produced in the same manner as the production method of the polyester resin (A1) described above.
[0074] The polyester resin (B1) may or may not have crystallinity, but is preferably an amorphous polyester resin from the viewpoint of heat-resistant storage stability. The amorphous polyester resin can be obtained by increasing the content of a branched monomer, for example, an alkylene oxide adduct of a bisphenol, in the alcohol component (x) and the carboxylic acid component (y) used.
[0075] The polyester resin (B1) may be any one of a linear polyester resin, a crosslinked polyester resin, and a mixture of a linear polyester resin and a crosslinked polyester resin, but from the viewpoint of low-temperature fixability, a linear polyester resin is preferred.
[0076] Glass transition temperature (Tg B1 ) is preferably from 50 to 80°C, more preferably from 50 to 70°C, and even more preferably from 55 to 65°C, from the viewpoints of low-temperature fixability, water resistance, and durability. The Tg is measured by using a DSC according to the method (DSC method) specified in ASTM D3418-82.
[0077] The peak top molecular weight (hereinafter sometimes abbreviated as Mp) of the polyester resin (B1) is preferably from 2,000 to 200,000, more preferably from 2,500 to 100,000, further preferably from 3,000 to 30,000, and particularly preferably from 5,000 to 10,000, from the viewpoints of low-temperature fixability and heat-resistant storage stability. The Mp of (B1) is measured using GPC under the same conditions as above.
[0078] The vinyl resin (B2) is a polymer having a monomer having a double bond as a constituent monomer, and is not particularly limited as long as the acid value is less than 1 mgKOH / g. Examples of the vinyl resin include crystalline vinyl resins and amorphous vinyl resins, and crystalline vinyl resins are preferred from the viewpoints of low-temperature fixability and water resistance. The term "crystalline" in crystalline vinyl resin refers to a differential scanning calorimetry (DSC) curve having a maximum and an endothermic peak during the temperature rise process in the DSC curve obtained by differential scanning calorimetry, whereas "amorphous" refers to the absence of an endothermic peak in the DSC curve.
[0079] From the viewpoints of crystallinity and low-temperature fixability, the crystalline vinyl resin is preferably a polymer having, as a constituent monomer, a monomer (a) which is a (meth)acrylate having a chain hydrocarbon group and having 21 to 40 carbon atoms and / or a vinyl ester having a chain hydrocarbon group and having 21 to 40 carbon atoms. If the carbon number of the monomer (a) is 21 or more, the heat-resistant storage stability may be good, and if the carbon number is 40 or less, the low-temperature fixability may be good. In the present invention, "(meth)acrylic" means methacrylic acid or acrylic acid, and "(meth)acrylate" means methacrylate or acrylate.
[0080] Examples of the monomer (a) include (meth)acrylates having a chain hydrocarbon group and a carbon number of 21 to 40 and / or vinyl esters having a chain hydrocarbon group and a carbon number of 21 to 40. Examples of the (meth)acrylates having a chain hydrocarbon group and a carbon number of 21 to 40 include (meth)acrylates having a linear alkyl group (carbon number of 18 to 36) [octadecyl (meth)acrylate (stearyl (meth)acrylate), nonadecyl (meth)acrylate, acrylate (meth) ... cosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, montanyl (meth)acrylate, triacontyl (meth)acrylate, dotriacontyl (meth)acrylate, and the like], and (meth)acrylates having a branched alkyl group (having 18 to 36 carbon atoms) [2-decyltetradecyl (meth)acrylate, and the like]. Examples of vinyl esters having a chain hydrocarbon group and having 21 to 40 carbon atoms include vinyl esters having a linear alkyl group (having 18 to 36 carbon atoms) [for example, vinyl stearate, vinyl behenate, vinyl triacontanoate, vinyl hexatriacontanoate, etc.] and vinyl esters having a branched alkyl group (having 18 to 36 carbon atoms). Among these, from the viewpoint of crystallinity, preferred are (meth)acrylates having a linear alkyl group (having 18 to 36 carbon atoms) and vinyl esters having a linear alkyl group (having 18 to 36 carbon atoms), more preferred are (meth)acrylates having a linear alkyl group (having 18 to 30 carbon atoms), even more preferred are octadecyl (meth)acrylate, eicosyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate and triacontyl (meth)acrylate, particularly preferred are octadecyl acrylate (stearyl acrylate), eicosyl acrylate, behenyl acrylate and lignoceryl acrylate, and most preferred is behenyl acrylate. The monomer (a) may be used alone or in combination of two or more kinds.
[0081] The crystalline vinyl resin may contain a monomer (b) other than the monomer (a) as a constituent monomer. As the monomer (b), a styrene-based monomer (b1), a (meth)acrylic-based monomer (b2) other than the monomer (a), a vinyl ester monomer (b3) other than the monomer (a), an aliphatic hydrocarbon-based vinyl monomer (b4), and a monomer (b5) having at least one functional group selected from the group consisting of a nitrile group, a urethane group, a urea group, an amide group, an imide group, an allophanate group, and a biuret group and an ethylenically unsaturated bond are preferable as the constituent monomer. The monomer (b) may be used alone or in combination of two or more kinds.
[0082] Examples of the styrene-based monomer (b1) include styrene and alkylstyrenes having an alkyl group with 1 to 3 carbon atoms (eg, α-methylstyrene and p-methylstyrene).
[0083] Examples of the (meth)acrylic monomer (b2) include alkyl (meth)acrylates having an alkyl group with 1 to 17 carbon atoms [methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, etc.], hydroxyalkyl (meth)acrylates having an alkyl group with 1 to 17 carbon atoms [2-hydroxypropyl acrylate, 2-hydroxyethyl (meth)acrylate, ethyl-2-(hydroxymethyl)acrylate, etc.], and hydroxyalkyl (meth)acrylates having an alkyl group with 1 to 17 carbon atoms [2-hydroxypropyl acrylate, 2-hydroxyethyl (meth)acrylate, ethyl-2-(hydroxymethyl)acrylate, etc.]. and esters of unsaturated carboxylic acids having 8 to 20 carbon atoms and polyhydric alcohols [ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, etc.].
[0084] Examples of the vinyl ester monomer (b3) include aliphatic vinyl esters having 4 to 15 carbon atoms (such as vinyl acetate, vinyl propionate, and isopropenyl acetate) and aromatic vinyl esters having 9 to 15 carbon atoms (such as methyl-4-vinylbenzoate).
[0085] Examples of the aliphatic hydrocarbon vinyl monomer (b4) include ethylene, propylene, butene, butadiene, isoprene, and 1,5-hexadiene.
[0086] Examples of the monomer (b5) having at least one functional group selected from the group consisting of a nitrile group, a urethane group, a urea group, an amide group, an imide group, an allophanate group, and a biuret group, and an ethylenically unsaturated bond, include a monomer (b51) having a nitrile group, a monomer (b52) having a urethane group, a monomer (b53) having a urea group, a monomer (b54) having an amide group, a monomer (b55) having an imide group, a monomer (b56) having an allophanate group, and a monomer (b57) having a biuret group.
[0087] Examples of the monomer (b51) having a nitrile group include acrylonitrile and methacrylonitrile.
[0088] Examples of the monomer (b52) having a urethane group include a monomer obtained by reacting an alcohol having 2 to 22 carbon atoms (2-hydroxyethyl methacrylate, vinyl alcohol, etc.) having an ethylenically unsaturated bond with an isocyanate having 1 to 30 carbon atoms by a known method, and a monomer obtained by reacting an alcohol having 1 to 26 carbon atoms with an isocyanate having 2 to 30 carbon atoms by a known method. Note that in this specification, the number of carbon atoms in a compound and structure having an isocyanate group does not include the number of carbon atoms contained in the isocyanate (NCO). Examples of isocyanates having 1 to 30 carbon atoms include monoisocyanate compounds (benzenesulfonyl isocyanate, tosyl isocyanate, phenyl isocyanate, p-chlorophenyl isocyanate, butyl isocyanate, hexyl isocyanate, t-butyl isocyanate, cyclohexyl isocyanate, octyl isocyanate, 2-ethylhexyl isocyanate, dodecyl isocyanate, adamantyl isocyanate, 2,6-dimethylphenyl isocyanate, 3,5-dimethylphenyl isocyanate, and 2,6-dipropylphenyl isocyanate, etc.), aliphatic diisocyanate compounds (trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylethylene diisocyanate, etc.), and cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated tetramethylxylylene diisocyanate, etc.) and aromatic diisocyanates. Examples of the isocyanate include diisocyanate compounds (phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate). Examples of alcohols having 1 to 26 carbon atoms include methanol, ethanol, propanol, isopropyl alcohol, butanol, t-butyl alcohol, pentanol, heptanol, octanol, 2-ethylhexanol, nonanol, decanol, undecyl alcohol, lauryl alcohol, dodecyl alcohol, myristyl alcohol, pentadecyl alcohol, cetanol, heptadecanol, stearyl alcohol, isostearyl alcohol, elaidyl alcohol, oleyl alcohol, linoleyl alcohol, linolenyl alcohol, nonadecyl alcohol, heneicosanol, behenyl alcohol, and erucyl alcohol. Examples of the isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond include 2-isocyanatoethyl (meth)acrylate, 2-[0-(1'-methylpropylideneamino)carboxyamino]ethyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, and 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate.
[0089] Examples of the monomer (b53) having a urea group include monomers obtained by reacting an amine having 3 to 22 carbon atoms [monovalent amines include, for example, primary amines (normal butylamine, t-butylamine, propylamine, isopropylamine, etc.), secondary amines (diethylamine, dinormal propylamine, dinormal butylamine, etc.), aniline, cyclohexylamine, etc.] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method.
[0090] Examples of the monomer (b54) having an amide group include monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 3 to 30 carbon atoms (such as acrylic acid and methacrylic acid) having an ethylenically unsaturated bond by a known method.
[0091] Examples of the monomer (b55) having an imide group include a monomer obtained by reacting ammonia with a carboxylic anhydride having 4 to 10 carbon atoms and an ethylenically unsaturated bond (maleic anhydride, diacrylic anhydride, etc.) by a known method, and a monomer obtained by reacting a primary amine having 1 to 30 carbon atoms with a carboxylic anhydride having 4 to 10 carbon atoms and an ethylenically unsaturated bond by a known method.
[0092] The monomer (b56) having an allophanate group may be, for example, a monomer obtained by reacting a monomer (b52) having a urethane group with an isocyanate having 1 to 30 carbon atoms by a known method.
[0093] Examples of the monomer (b57) having a biuret group include a monomer obtained by reacting a monomer (b53) having a urea group with an isocyanate having 1 to 30 carbon atoms by a known method.
[0094] Among these monomers (b), from the viewpoint of charge retention rate and heat-resistant storage stability, preferred are styrene-based monomers (b1), (meth)acrylic monomers (b2) other than monomer (a), and monomers (b5) having at least one functional group selected from the group consisting of a nitrile group, a urethane group, a urea group, an amide group, an imide group, an allophanate group, and a biuret group, and an ethylenically unsaturated bond, more preferred are styrene, alkyl (meth)acrylates having an alkyl group of 1 to 17 carbon atoms, and monomers (b51) having a nitrile group, and even more preferred are styrene, methyl (meth)acrylate, butyl (meth)acrylate, acrylonitrile, and methacrylonitrile.
[0095] The weight ratio of the monomer (a) in the monomers constituting the crystalline vinyl resin is preferably 30% by weight or more, more preferably 40% by weight or more, and even more preferably 60% by weight, based on the total weight of the monomers constituting the crystalline vinyl resin. When the weight ratio of the monomer (a) is 30% by weight or more, the crystallinity and water resistance are good. On the other hand, the upper limit is preferably 99% by weight or less, more preferably 95% by weight or less, and even more preferably 80% by weight or less, from the viewpoint of achieving both low-temperature fixability, hot offset resistance, and heat-resistant storage stability.
[0096] From the viewpoint of heat-resistant storage stability, the monomers constituting the crystalline vinyl resin preferably contain a monomer (b). The weight ratio of the monomer (b) in the monomers constituting the crystalline vinyl resin is preferably 1 to 70% by weight, more preferably 1 to 60% by weight, further preferably 5 to 60% by weight, and particularly preferably 5 to 40% by weight, based on the total weight of the monomers constituting (B).
[0097] The vinyl resin (B2) can be produced by polymerizing a monomer composition by a known method (such as the method described in JP-A-5-117330). For example, it can be synthesized by a solution polymerization method in which the above-mentioned monomers are reacted with a radical reaction initiator (such as azobisisobutyronitrile) in a solvent (such as toluene). The radical reaction initiator may be a known radical reaction initiator (c). The radical reaction initiator (c) is not particularly limited, and examples thereof include inorganic peroxides (c1), organic peroxides (c2), and azo compounds (c3). These radical reaction initiators may also be used in combination.
[0098] The inorganic peroxide (c1) is not particularly limited, but examples thereof include hydrogen peroxide, ammonium persulfate, potassium persulfate, and sodium persulfate.
[0099] The organic peroxide (c2) is not particularly limited, and examples thereof include benzoyl peroxide, di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, α,α-bis(t-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-bis(t-butylperoxy)hexane, di-t-hexyl peroxide, 2,5-dimethyl-2,5-di-t-butylperoxyhexyne-3, acetyl peroxide, isobutyryl peroxide, octanyl peroxide, decanolyl peroxide, Examples of peroxyalkylene oxides include lauroyl peroxide, 3,3,5-trimethylhexanoyl peroxide, m-toluyl peroxide, t-butyl peroxyisobutyrate, t-butyl peroxyneodecanoate, cumyl peroxyneodecanoate, t-butyl peroxy-2-ethylhexanoate, t-butyl peroxy-3,5,5-trimethylhexanoate, t-butyl peroxylaurate, t-butyl peroxybenzoate, t-butyl peroxyisopropyl monocarbonate, and t-butyl peroxyacetate.
[0100] The azo compound (c3) is not particularly limited, but examples thereof include 2,2'-azobis-(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobisisobutyronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile, and azobisisobutyronitrile.
[0101] Endothermic peak top temperature (Tm B2 From the viewpoints of heat-resistant storage stability and low-temperature fixability, the endothermic peak top temperature is preferably 40 to 100° C., and more preferably 45 to 90° C. When the endothermic peak top temperature is 40° C. or higher, the heat-resistant storage stability is good, and when it is 100° C. or lower, the low-temperature fixability is good. However, the endothermic peak top temperature (Tm B2) is the peak top temperature of the endothermic peak of vinyl resin (B2) during the second heating process, in which crystalline vinyl resin (B) is heated for the first time from 20°C to 150°C at 10°C / min using DSC, then cooled from 150°C to 0°C at 10°C / min, and then heated from 0°C to 150°C at 10°C / min.
[0102] Endothermic peak top temperature (Tm B2 ) is a value measured using a DSC under the following conditions. As the differential scanning calorimeter, for example, DSC Q20 manufactured by TA Instruments Co., Ltd. can be used. <Measurement conditions> (1) Heat from 20°C to 150°C at 10°C / min (2) Cool to 0°C at 10°C / min (3) Heat up to 150°C at 10°C / min. (4) Each endothermic peak in the differential scanning calorimetry curve measured in the process of (3) is analyzed.
[0103] The number average molecular weight of the vinyl resin (B2) is preferably from 1,000 to 300,000 from the viewpoints of heat-resistant storage stability and low-temperature fixability.
[0104] The weight average molecular weight of the vinyl resin (B2) is preferably from 1,000 to 300,000, and more preferably from 17,000 to 60,000, from the viewpoints of heat-resistant storage stability and low-temperature fixability. The Mn and Mw of the vinyl resin (B2) can be measured by the method described above.
[0105] The method for producing the toner binder of the present invention comprises the steps of: catalyst The mixing method is not particularly limited as long as it includes a step of reacting the polyester resin (A1) with the epoxy compound (E) in the presence of (F), and examples of known mixing methods include powder mixing, melt mixing, and solvent mixing. catalyst(F) may be mixed together with other necessary toner raw materials at the same time when the toner is produced. Examples of the solvent used in the solvent mixing include ethyl acetate, tetrahydrofuran, methyl ethyl ketone, and acetone.
[0106] Examples of a mixer for powder mixing include a Henschel mixer, a Nauta mixer, and a Banbury mixer, with a Henschel mixer being preferred. Examples of mixing devices for melt mixing include batch mixing devices such as reaction tanks and continuous mixing devices. Continuous mixing devices are preferred for uniform mixing in a short time at an appropriate temperature. Examples of continuous mixing devices include static mixers, extruders, continuous kneaders, and three-roll machines. Examples of the solvent mixing method include a method in which the polyester resin (A1) and the resin (B) are dissolved in a solvent (ethyl acetate, tetrahydrofuran, acetone, etc.), homogenized, then the solvent is removed and pulverized, and a method in which the polyester resin (A1) and the resin (B) are dissolved in a solvent (ethyl acetate, tetrahydrofuran, acetone, etc.), dispersed in water, then granulated and the solvent is removed.
[0107] Of the melt mixing and solvent mixing, the melt mixing is preferred since it allows uniform mixing and does not require solvent removal. Among these, the method of melt-mixing the resin (B) and the polyester resin (A1) while reacting the polyester resin (A1) with the epoxy compound (E) is preferred.
[0108] As a method for reacting the polyester (A1) with the epoxy compound (E) while melt-mixing the resin (B) with the polyester resin (A1), a mixture of the polyester resin (A1) and the resin (B) is injected into a twin-screw extruder at a constant speed, and catalyst In one method, the polyester resin (A1) and the epoxy compound (E) are also injected at a constant speed, and the reaction is carried out while the mixture is kneaded and conveyed at a temperature of 100 to 200°C. In another method, the polyester resin (A1) and the resin (B) are charged in a batch type mixer such as a reaction tank, melted, and uniformly mixed, and then catalystand a method in which (F) and epoxy compound (E) are charged and crosslinked at a temperature of 100 to 200° C. In this case, the polyester resin (A1) and resin (B), which are reaction raw materials to be charged or injected into a twin-screw extruder or a reaction tank, may be directly injected into the extruder or reaction tank as they are without cooling the reacted resins from a molten state, or the resins may be produced once, cooled, pulverized, and then fed to the twin-screw extruder or reaction tank.
[0109] In the toner binder production method of the present invention (before the reaction of the polyester resin (A1) with the epoxy compound (E)), the weight ratio of the polyester resin (A1) to the resin (B) [(A1):(B)] is preferably 20:80 to 80:20, and more preferably 40:60 to 70:30, from the viewpoints of water resistance, durability, and low-temperature fixability.
[0110] From the viewpoints of uniformity of crosslinking and productivity, the temperature at which the polyester resin (A1) and the epoxy compound (E) are reacted is preferably 100 to 200° C., more preferably 130 to 190° C., and even more preferably 150 to 180° C. If the crosslinking temperature is 200° C. or lower, decomposition of the vinyl resin is unlikely to occur and heat resistance storage stability is good, while if the crosslinking temperature is 100° C. or higher, the resin viscosity is low and uniformity is good.
[0111] The time for reacting the polyester resin (A1) with the epoxy compound (E) using a continuous mixer such as a twin-screw extruder is preferably 1 to 20 minutes, more preferably 2 to 18 minutes, from the viewpoints of uniformity of crosslinking and productivity. The time for reacting the polyester resin (A1) with the epoxy compound (E) using a batch-type mixing device such as a reaction tank is, from the viewpoints of uniformity of crosslinking and productivity, preferably 30 to 600 minutes, more preferably 60 to 540 minutes, even more preferably 90 to 480 minutes, and particularly preferably 120 to 420 minutes.
[0112] From the viewpoints of low-temperature fixability, hot offset resistance and durability, the reaction rate of the polyester resin (A1) and the epoxy compound (E) is preferably 90% or more, and more preferably 95% or more.
[0113] In the present invention, catalyst The steps other than the step of reacting the polyester resin (A1) with the epoxy compound (E) in the presence of (F) are not particularly limited, and a general toner binder production process can be adopted. For example, when the above-mentioned process is carried out by melt mixing, a process of taking out the toner binder can be provided, and when the above-mentioned crosslinking process is carried out by solvent mixing, a process of taking out the toner binder after removing the solvent and pulverizing it can be provided. When the above-mentioned process is carried out by solvent mixing, a process of dispersing in water, granulating and removing the solvent can be provided. Furthermore, a process of mixing additives with the obtained granular toner binder by a known method can also be provided.
[0114] The endothermic peak top temperature (Tm C From the viewpoints of low-temperature fixability and heat-resistant storage stability, the endothermic peak top temperature is preferably 40 to 100° C., and more preferably 45 to 90° C. When the endothermic peak top temperature is 40° C. or higher, the heat-resistant storage stability is good, and when it is 100° C. or lower, the low-temperature fixability is good. However, the endothermic peak top temperature (Tm C ) is the endothermic peak top temperature of the toner binder during the second heating process, which is performed by using a differential scanning calorimeter (DSC) to heat the toner binder for the first time from 20°C to 150°C at a rate of 10°C / min, then cooling from 150°C to 0°C at a rate of 10°C / min, and then heating from 0°C to 150°C at a rate of 10°C / min. C ) is the endothermic peak top temperature (Tm B2 ) can be measured in the same manner. Toner binder endothermic peak top temperature (Tm CThe endothermic peak top temperature (Tm) can be adjusted to the above-mentioned preferred range by adjusting the number of carbon atoms of the monomer (a) constituting the vinyl resin (B2) or by adjusting the weight ratio of the monomer (a) constituting the vinyl resin (B2). In general, the endothermic peak top temperature (Tm) can be increased by increasing the number of carbon atoms of the monomer (a), increasing the weight ratio of the monomer (a), or increasing the weight average molecular weight of the vinyl resin (B2). C ) tends to rise.
[0115] Glass transition temperature (Tg C From the viewpoint of water resistance and low-temperature fixability, the temperature is preferably from -35 to 60°C, more preferably from -15 to 58°C, further preferably from 15 to 55°C, and particularly preferably from 35 to 55°C. The Tg is measured by using a differential scanning calorimeter (DSC) in accordance with the method specified in ASTM D3418-82. C For example, a DSC Q20 manufactured by TA Instruments can be used for measuring the glass transition temperature (Tg C ) can be measured under the following conditions. <Measurement conditions> (1) Heat from 30°C to 150°C at 20°C / min (2) Hold at 150°C for 10 minutes (3) Cool to -35°C at 20°C / min (4) Keep at -35℃ for 10 minutes (5) Heat up to 150°C at 20°C / min. (6) The differential scanning calorimetry curve measured in the process of (5) is analyzed.
[0116] The acid value of the toner binder is preferably 4.0 to 50.0 mgKOH / g, more preferably 4.0 to 30.0 mgKOH / g, and further preferably 4.0 to 20.0 mgKOH / g, from the viewpoints of heat-resistant storage stability, durability, water resistance, and charge retention rate. The acid value of the toner binder can be determined in the same manner as in the polyester resin (A1).
[0117] When producing a toner using the toner binder obtained by the method of the present invention, in addition to the toner binder of the present invention, one or more known additives selected from a colorant, a release agent, a charge control agent, a fluidizing agent, etc. may be used as necessary.
[0118] As the colorant, all of the dyes and pigments used as toner colorants can be used. For example, carbon black, iron black, Sudan Black SM, Fast Yellow G, Benzidine Yellow, Pigment Yellow, India Fast Orange, Irgasin Red, Paranitroaniline Red, Toluidine Red, Carmine FB, Pigment Orange R, Lake Red 2G, Rhodamine FB, Rhodamine B Lake, Methyl Violet B Lake, Phthalocyanine Blue, Pigment Blue, Brilliant Green, Phthalocyanine Green, Oil Yellow GG, Kayaset YG, Orazol Brown B, and Oil Pink OP can be mentioned, and the colorant may be a single one or a mixture of two or more kinds. In addition, if necessary, magnetic powder (powder of ferromagnetic metals such as iron, cobalt, nickel, etc., or compounds such as magnetite, hematite, and ferrite) can be contained to function as a colorant. The content of the colorant is preferably 1 to 40 parts by weight, more preferably 3 to 10 parts by weight, based on 100 parts by weight of the toner binder. When a magnetic powder is used, the content is preferably 20 to 150 parts by weight, more preferably 40 to 120 parts by weight, based on 100 parts by weight of the toner binder.
[0119] The release agent preferably has a flow softening point (T1 / 2) of 50 to 170°C as measured by a flow tester. Examples of the release agent include aliphatic hydrocarbon waxes such as polyolefin wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, as well as oxides thereof, carnauba wax, montan wax, and deacidified waxes thereof, ester wax, fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts.
[0120] The flow softening point (T1 / 2) of the release agent is a value measured under the following conditions. <How to measure flow softening point (T1 / 2)> Test force: Using an extrusion-type capillary rheometer flow tester [e.g., CFT-500D, manufactured by Shimadzu Corporation], 1 g of the measurement sample is heated at a temperature increase rate of 6°C / min while applying a load of 1.96 MPa with the plunger, and extruding it from a nozzle with a diameter of 1 mm and a length of 1 mm. A graph is drawn of "plunger drop (flow value)" versus "temperature," and the temperature corresponding to 1 / 2 of the maximum value of the plunger drop is read from the graph. This value (the temperature when half of the measurement sample has flowed out) is the flow softening point (T1 / 2).
[0121] Examples of polyolefin waxes include (co)polymers of olefins (e.g., ethylene, propylene, 1-butene, isobutylene, 1-hexene, 1-dodecene, 1-octadecene, and mixtures thereof) [including those obtained by (co)polymerization and those obtained by further thermal degradation thereof] (e.g., low molecular weight polypropylene, low molecular weight polyethylene, low molecular weight polypropylene-polyethylene copolymer), oxides of olefin (co)polymers with oxygen and / or ozone, maleic acid modified products of olefin (co)polymers [e.g., maleic acid and its derivatives (maleic anhydride, monomethyl maleate, monobutyl maleate, dimethyl maleate, etc.) modified products], copolymers of olefins and unsaturated carboxylic acids [(meth)acrylic acid, itaconic acid, maleic anhydride, etc.] and / or unsaturated carboxylic acid alkyl esters [(meth)acrylic acid alkyl (alkyl having 1 to 18 carbon atoms) esters and maleic acid alkyl (alkyl having 1 to 18 carbon atoms) esters, etc.], and the like.
[0122] Examples of microcrystalline waxes include Hi-Mic-2095, Hi-Mic-1090, Hi-Mic-1080, Hi-Mic-1070, Hi-Mic-2065, Hi-Mic-1045, and Hi-Mic-2045 manufactured by Nippon Seiro Co., Ltd.
[0123] Examples of paraffin waxes include Paraffin WAX-155, Paraffin WAX-150, Paraffin WAX-145, Paraffin WAX-140, Paraffin WAX-135, HNP-3, HNP-5, HNP-9, HNP-10, HNP-11, HNP-12, and HNP-51, manufactured by Nippon Seiro Co., Ltd.
[0124] An example of the Fischer-Tropsch wax is Sasolwax C80 manufactured by Sasol.
[0125] An example of carnauba wax is Refined Carnauba Wax Special No. 1 manufactured by Kato Yoko Co., Ltd.
[0126] Examples of the ester wax include fatty acid ester waxes (for example, Nissan Electol WEP-2, WEP-3, WEP-4, WEP-5, and WEP-8 manufactured by NOF Corporation).
[0127] The higher alcohols include aliphatic alcohols having 30 to 50 carbon atoms, such as triacontanol. The fatty acids include fatty acids having 30 to 50 carbon atoms, such as triacontancarboxylic acid.
[0128] Examples of fatty acid amides include Diamid Y and Diamid 200 manufactured by Mitsubishi Chemical Corporation.
[0129] The charge control agent may be either a positively charged charge control agent or a negatively charged charge control agent, and examples of the charge control agent include nigrosine dyes, triphenylmethane dyes containing a tertiary amine as a side chain, quaternary ammonium salts, polyamine resins, imidazole derivatives, polymers containing a quaternary ammonium base, metal-containing azo dyes, copper phthalocyanine dyes, metal salicylic acid salts, boron complexes of benzilic acid, sulfonic acid group-containing polymers, fluorine-containing polymers, and halogen-substituted aromatic ring-containing polymers.
[0130] The fluidizing agent may be silica, titania, alumina, calcium carbonate, fatty acid metal salt, silicone resin particles, fluororesin particles, etc., and may be used in combination of two or more. From the viewpoint of the chargeability of the toner, silica is preferred. Moreover, from the viewpoint of the transferability of the toner, the silica is preferably hydrophobic silica.
[0131] The content of the toner binder in the toner is preferably from 30 to 97% by weight, more preferably from 40 to 95% by weight, and further preferably from 45 to 92% by weight, based on the weight of the toner. The content of the colorant is preferably 0.05 to 60% by weight, more preferably 0.1 to 55% by weight, and further preferably 0.5 to 50% by weight, based on the weight of the toner. The content of the release agent is preferably 0 to 30% by weight, more preferably 0.5 to 20% by weight, and further preferably 1 to 10% by weight, based on the weight of the toner. The content of the charge control agent is preferably 0 to 20% by weight, more preferably 0.1 to 10% by weight, and further preferably 0.5 to 7.5% by weight, based on the weight of the toner. The content of the fluidizing agent is preferably 0 to 10% by weight, more preferably 0 to 5% by weight, and further preferably 0.1 to 4% by weight, based on the toner weight. The total content of the additives is preferably 3 to 70% by weight, more preferably 4 to 58% by weight, and further preferably 5 to 50% by weight, based on the toner weight. By setting the composition ratio of the toner within the above range, it is possible to easily obtain a toner having good charge retention rate (particularly charge retention rate under high temperature and high humidity conditions) and heat-resistant storage stability.
[0132] The toner may be obtained by any of the known methods such as a kneading and pulverizing method, an emulsion phase inversion method, and a polymerization method. For example, when a toner is obtained by a kneading and pulverizing method, the components constituting the toner except for the fluidizing agent are dry-blended, melt-kneaded, then coarsely pulverized, and finally, the toner is pulverized using a jet mill pulverizer or the like, and further classified to obtain fine particles having a volume average particle size (D50) of preferably 5 to 20 μm, and then the fluidizing agent is mixed therein to produce the toner. The volume average particle size (D50) is measured using a Coulter counter {for example, trade name: Multisizer III [manufactured by Beckman Coulter, Inc.]}.
[0133] In addition, when the toner is obtained by the emulsion phase inversion method, the components constituting the toner except for the fluidizing agent are dissolved or dispersed in an organic solvent, and then emulsified by adding water or the like, followed by separation and classification to produce the toner. The volume average particle size of the toner is preferably 3 to 15 μm.
[0134] The toner is mixed with carrier particles such as iron powder, glass beads, nickel powder, ferrite, magnetite, and ferrite coated with resin (acrylic resin, silicone resin, etc.) as necessary, and used as a developer for an electric latent image. When carrier particles are used, the weight ratio of the toner to the carrier particles is preferably 1 / 99 to 99 / 1. Also, the toner can be rubbed against a member such as a charging blade instead of the carrier particles to form an electric latent image. The toner does not necessarily need to contain carrier particles.
[0135] The toner is fixed to a support (paper, polyester film, etc.) to form a recording material by a copier, printer, etc. As a method for fixing to a support, a known heat roll fixing method, flash fixing method, etc. can be used.
[0136] The toner and toner binder of the present invention are used for developing electrostatic images or magnetic latent images in electrophotography, electrostatic recording, electrostatic printing, etc. More specifically, they are used for developing electrostatic images or magnetic latent images particularly suitable for full color. EXAMPLES
[0137] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto. In the following, "parts" refers to parts by weight unless otherwise specified.
[0138] <Production Example 1> [Production of polyester resin (A1-1)] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 721 parts of bisphenol A·PO 2-mol adduct, 101 parts of terephthalic acid, 53 parts of trimellitic anhydride, and 2.5 parts of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed and reacted for 2 hours under a nitrogen stream at 230°C while distilling off the water produced. Next, the reaction was carried out for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value of the reaction product was less than 1 mgKOH / g, the temperature was lowered to 180°C. 205 parts of adipic acid were further added and reacted for 2 hours, and then the reaction was carried out for 3 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value was 49 mgKOH / g, the product was taken out to obtain polyester resin (A1-1).
[0139] <Production Example 2> [Production of polyester resin (A1-2)] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 695 parts of bisphenol A·EO 2-mol adduct, 182 parts of terephthalic acid, 12 parts of trimethylolpropane, and 2.5 parts of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed and reacted for 2 hours under a nitrogen stream at 230°C while distilling off the water produced. Next, the reaction was carried out for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value of the reaction product was less than 1 mgKOH / g, the temperature was lowered to 180°C. Further, 195 parts of adipic acid was added and reacted for 2 hours, and then the reaction was carried out for 3 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value was 28 mgKOH / g, the reaction product was taken out to obtain polyester resin (A1-2).
[0140] <Production Example 3> [Production of polyester resin (A1-3)] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 135 parts of bisphenol A·PO 2-mol adduct, 604 parts of bisphenol A·PO 3-mol adduct, 130 parts of terephthalic acid, 76 parts of adipic acid, 28 parts of trimellitic anhydride, 2.5 parts of titanium diisopropoxy bistriethanolamine were added as a condensation catalyst, and the mixture was reacted for 2 hours under a nitrogen stream at 230°C while distilling off the water produced. Next, the mixture was reacted for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value of the reaction product was less than 1 mgKOH / g, the temperature was lowered to 180°C. 77 parts of trimellitic anhydride were further added, and the mixture was reacted for 1 hour under normal pressure, and then removed to obtain polyester resin (A1-3).
[0141] <Production Example 4> [Production of polyester resin (A1-4)] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 708 parts of bisphenol A·EO 2-mol adduct, 146 parts of terephthalic acid, 85 parts of adipic acid, 31 parts of trimellitic anhydride, and 2.5 parts of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed and reacted for 2 hours under a nitrogen stream at 230°C while distilling off the water produced. Next, the reaction was carried out for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value of the reaction product was less than 1 mgKOH / g, the temperature was lowered to 180°C. 85 parts of trimellitic anhydride was placed and reacted for 1 hour under normal pressure, and then the reaction mixture was removed to obtain polyester resin (A1-4).
[0142] <Production Example 5> [Production of polyester resin (A1-5)] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 763 parts of bisphenol A·EO 2-mol adduct, 157 parts of terephthalic acid, 92 parts of adipic acid, 33 parts of trimellitic anhydride, and 2.5 parts of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed and reacted for 2 hours under a nitrogen stream at 230°C while distilling off the water produced. Next, the reaction was carried out for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value of the reaction product was less than 1 mgKOH / g, the temperature was lowered to 180°C. Further, 13 parts of trimellitic anhydride were placed and reacted for 1 hour under normal pressure, and then the product was taken out to obtain polyester resin (A1-5).
[0143] <Production Example 6> [Production of polyester resin (A1-6)] In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, 553 parts of 3-methyl-1,5-pentanediol, 19 parts of trimethylolpropane, 374 parts of terephthalic acid, 300 parts of adipic acid, and 2.5 parts of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed and subjected to an esterification reaction at normal pressure at 220° C. After confirming that the acid value of the reaction product was less than 40 mgKOH / g, the reaction was carried out at 220° C. under reduced pressure of 0.5 to 2.5 kPa for 5 hours, and 93 parts of 3-methyl-1,5-pentanediol and 155 parts of condensation water were collected. Since the acid value confirmed at that point was less than 21 mgKOH / g, the reaction product was taken out and a polyester resin (A1-6) was obtained.
[0144] <Production Example 7> [Production of polyester resin (A1-7)] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 703 parts of bisphenol A·EO 2-mol adduct, 145 parts of terephthalic acid, 85 parts of adipic acid, 31 parts of trimellitic anhydride, and 2.5 parts of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed and reacted for 2 hours under a nitrogen stream at 230°C while distilling off the water produced. Next, the reaction was carried out for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value of the reaction product was less than 1 mgKOH / g, the temperature was lowered to 180°C. Further, 90 parts of trimellitic anhydride was placed and reacted for 1 hour under normal pressure, and then the reaction was removed to obtain polyester resin (A1-7).
[0145] The compositions and physical properties of the polyester resins (A1) obtained in Production Examples 1 to 7 are shown in Table 1.
[0146] [Table 1]
[0147] <Production Example 8> [Production of polyester resin (B1-1)] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 193 parts of bisphenol A·PO 2-mol adduct, 559 parts of bisphenol A·EO 2-mol adduct, 312 parts of terephthalic acid, and 2.5 parts of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed and reacted for 2 hours under a nitrogen stream at 230°C while distilling off the water produced. Next, the reaction was carried out for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value of the reaction product was less than 1 mgKOH / g, it was removed and polyester resin (B1-1) was obtained.
[0148] <Production Example 9> [Production of polyester resin (B1-2)] In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 684 parts of bisphenol A·PO 2-mol adduct, 85 parts of bisphenol A·PO 3-mol adduct, 261 parts of terephthalic acid, 29 parts of isophthalic acid, and 2.5 parts of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed and reacted for 2 hours under a nitrogen stream at 230°C while distilling off the water produced. Next, the reaction was carried out for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value of the reaction product was less than 1 mgKOH / g, it was removed and polyester resin (B1-2) was obtained.
[0149] <Comparative Manufacturing Example 1> In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 672 parts of bisphenol A·PO 2-mol adduct, 84 parts of bisphenol A·PO 3-mol adduct, 257 parts of terephthalic acid, 29 parts of isophthalic acid, and 2.5 parts of titanium diisopropoxy bistriethanolamine as a condensation catalyst were placed and reacted for 2 hours under a nitrogen stream at 230°C while distilling off the water produced. Next, the reaction was carried out for 5 hours under a reduced pressure of 0.5 to 2.5 kPa, and after confirming that the acid value of the reaction product was less than 1 mgKOH / g, the temperature was lowered to 180°C. Further, 17 parts of trimellitic anhydride were placed and reacted for 1 hour under normal pressure, and then the product was taken out to obtain polyester resin (B1'-1).
[0150] The compositions and physical properties of the polyester resins (B1) and (B1′) obtained in Production Examples 8 and 9 and Comparative Production Example 1 are shown in Table 2.
[0151] [Table 2]
[0152] <Production Example 10> [Production of vinyl resin (B2-1)] 138 parts of xylene was charged into the autoclave, and after replacing with nitrogen, the temperature was raised to 165°C in a sealed state with stirring. A mixed solution of 450 parts of behenyl acrylate [manufactured by NOF Corp., the same applies below], 150 parts of styrene [manufactured by Idemitsu Kosan Co., Ltd., the same applies below], 150 parts of acrylonitrile [manufactured by Nacalai Tesque Co., Ltd., the same applies below], 1.0 part of di-t-butyl peroxide [Perbutyl D, manufactured by NOF Corp., the same applies below], and 100 parts of xylene was adjusted to 60°C, and while controlling the temperature inside the autoclave to 165°C, it was dropped over 3 hours to polymerize. After dropping, the dropping line was washed with 12 parts of xylene. The temperature was further maintained at the same temperature for 0.5 hours, and the reaction rate of monomer (a) was confirmed. Since the reaction rate of the monomer (a) was less than 95%, 0.5 parts of di-t-butyl peroxide was further added to react until the reaction rate reached 95% or more. The solvent was removed at 165°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (B2-1).
[0153] <Production Example 11> [Production of vinyl resin (B2-2)] 138 parts of xylene was charged into the autoclave, and after replacing with nitrogen, the temperature was raised to 165°C in a sealed state with stirring. A mixed solution of 525 parts of stearyl acrylate [manufactured by NOF Corp., the same applies below], 150 parts of styrene, 75 parts of acrylonitrile, 0.2 parts of di-t-butyl peroxide, and 100 parts of xylene was adjusted to 60°C, and while controlling the temperature inside the autoclave to 165°C, it was dropped over 3 hours to polymerize. After dropping, the dropping line was washed with 12 parts of xylene. The same temperature was maintained for another 0.5 hours to confirm the reaction rate of monomer (a). Since the reaction rate of monomer (a) was less than 95%, 0.1 parts of di-t-butyl peroxide was further added and reacted until the reaction rate reached 95% or more. The solvent was removed at 165°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (B2-2).
[0154] <Production Example 12> [Synthesis of triacontyl acrylate] In a reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, an air inlet tube, a pressure reducing device, and a water reducing device, 50 parts of 1-triacontanol, 50 parts of toluene, 12 parts of acrylic acid, and 0.05 parts of hydroquinone were added and stirred to make the mixture homogenous. Then, 2 parts of paratoluenesulfonic acid were added, and the mixture was stirred for 30 minutes, and then the mixture was reacted for 5 hours while removing the water generated at 100°C while blowing in air at a flow rate of 30 mL / min. Then, the pressure in the reaction vessel was adjusted to 300 mmHg, and the reaction was continued for another 3 hours while removing the water generated. After cooling the reaction solution to room temperature, 30 parts of a 10% by weight aqueous sodium hydroxide solution was added, and the mixture was stirred for 1 hour, and then allowed to stand to separate the organic phase and the aqueous phase. The organic phase was collected by liquid separation and centrifugation, and 0.01 parts of hydroquinone was added, and the solvent was removed under reduced pressure while blowing in air to obtain triacontyl acrylate.
[0155] <Production Example 13> [Production of vinyl resin (B2-3)] 138 parts of xylene was charged into the autoclave, and after replacing with nitrogen, the temperature was raised to 165°C in a sealed state under stirring. A mixed solution of 600 parts of triacontyl acrylate obtained in Production Example 12, 75 parts of styrene, 75 parts of butyl acrylate [manufactured by Mitsubishi Chemical Corporation, the same applies below], 1.5 parts of di-t-butyl peroxide, and 100 parts of xylene was adjusted to 60°C, and while controlling the temperature inside the autoclave to 165°C, it was dropped over 3 hours to polymerize. After dropping, the dropping line was washed with 12 parts of xylene. The temperature was maintained for another 0.5 hours, and the reaction rate of monomer (a) was confirmed. Since the reaction rate of monomer (a) was less than 95%, 0.5 parts of di-t-butyl peroxide was further added and reacted until the reaction rate reached 95% or more. The solvent was removed at 165° C. for 5 hours under a reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (B2-3).
[0156] <Production Example 14> [Production of vinyl resin (B2-4)] 138 parts of xylene was charged into the autoclave, and after replacing with nitrogen, the temperature was raised to 165°C in a sealed state with stirring. A mixed solution of 300 parts of behenyl acrylate, 150 parts of stearyl acrylate, 125 parts of acrylonitrile, 75 parts of butyl acrylate, 100 parts of methyl methacrylate [manufactured by Sumitomo Chemical Co., Ltd., the same applies below], 0.5 parts of di-t-butyl peroxide, and 100 parts of xylene was adjusted to 60°C, and while controlling the temperature inside the autoclave to 165°C, it was dropped over 3 hours to polymerize. After dropping, the dropping line was washed with 12 parts of xylene. The temperature was maintained for another 0.5 hours, and the reaction rate of monomer (a) was confirmed. Since the reaction rate of monomer (a) was less than 95%, 0.2 parts of di-t-butyl peroxide was further added and reacted until the reaction rate reached 95% or more. The solvent was removed at 165° C. for 5 hours under a reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (B2-4).
[0157] <Production Example 15> [Production of vinyl resin (B2-5)] 138 parts of xylene was charged into the autoclave, and after replacing with nitrogen, the temperature was raised to 165°C in a sealed state with stirring. A mixed solution of 450 parts of behenyl acrylate, 75 parts of styrene, 225 parts of acrylonitrile, 0.5 parts of di-t-butyl peroxide, and 100 parts of xylene was adjusted to 60°C, and while controlling the temperature inside the autoclave at 165°C, it was dropped over 3 hours to polymerize. After dropping, the dropping line was washed with 12 parts of xylene. The same temperature was maintained for another 0.5 hours to confirm the reaction rate of monomer (a). Since the reaction rate of monomer (a) was less than 95%, 2.0 parts of di-t-butyl peroxide was further added and reacted until the reaction rate reached 95% or more. The solvent was removed at 165°C for 5 hours under reduced pressure of 0.5 to 2.5 kPa to obtain a crystalline vinyl resin (B2-5).
[0158] The compositions and physical properties of the vinyl resins (B2) obtained in Production Examples 10 to 15 are shown in Table 3.
[0159] [Table 3]
[0160] <Example 1> [Production of toner binder (C-1)] 50 parts of polyester resin (A1-1), 50 parts of polyester resin (B1-1), 2.2 parts of jER157S70 [bisphenol A novolac type epoxy resin, manufactured by Mitsubishi Chemical Corporation, epoxy equivalent 209, the same below] (E-1) and 0.1 parts of imidazole [manufactured by Fujifilm Wako Pure Chemical Industries, the same below] (F-1) were mixed and fed to a twin-screw kneader [Kurimoto Iron Works, Ltd., S5KRC kneader] at 80 kg / hour, and kneaded and extruded at 180°C and 90 rpm for 5 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-1). The glass transition temperature Tg of (C-1) was 1.0 g / h. C The temperature was 49.9°C, the acid value was 17.9 mg KOH / g, and the reaction rate was 99%.
[0161] <Example 2> [Production of toner binder (C-2)] 50 parts of polyester resin (A1-2), 50 parts of polyester resin (B1-2), 2.1 parts of jER157S70 (E-1) and 0.1 parts of 2-ethyl-4-methylimidazole [manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., the same applies below] (F-3) were mixed, fed to a twin-screw kneader at 80 kg / hour, and kneaded and extruded at 180°C and 90 rpm for 5 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-2). The glass transition temperature Tg of (C-2) was 1.0 g / h. C The temperature was 46.1°C, the acid value was 8.5 mgKOH / g, and the reaction rate was 98%.
[0162] <Example 3> [Production of toner binder (C-3)] 70 parts of polyester resin (A1-3), 30 parts of polyester resin (B1-1), 5.5 parts of jER157S70 (E-1) and 0.2 parts of 2-phenylimidazole (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., the same applies below) (F-2) were mixed and fed to a twin-screw kneader at 80 kg / hour, and kneaded and extruded at 160°C and 90 rpm for 2 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-3). The glass transition temperature Tg of (C-3) was CThe temperature was 53.0°C, the acid value was 14.4 mg KOH / g, and the reaction rate was 97%.
[0163] <Example 4> [Production of toner binder (C-4)] 70 parts of polyester resin (A1-4), 30 parts of polyester resin (B1-1), 6.0 parts of jER157S70 (E-1) and 0.2 parts of imidazole (F-1) were mixed and fed to a twin-screw kneader at 80 kg / hour, and kneaded and extruded at 150°C and 90 rpm for 2 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-4). The glass transition temperature Tg of (C-4) was C The temperature was 54.9°C, the acid value was 15.9 mg KOH / g, and the reaction rate was 95%.
[0164] <Example 5> [Production of toner binder (C-5)] 70 parts of polyester resin (A1-4), 30 parts of polyester resin (B1-1), 5.5 parts of EPPN-201 [phenol novolac type epoxy resin, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 193, the same applies below] (E-2) and 0.2 parts of imidazole (F-1) were mixed, fed to a twin-screw kneader at 80 kg / hour, and kneaded and extruded at 150°C and 90 rpm for 2 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-5). The glass transition temperature Tg of (C-5) was 1.0 g / h. C The temperature was 55.0°C, the acid value was 15.5 mgKOH / g, and the reaction rate was 99%.
[0165] <Example 6> [Production of toner binder (C-6)] 70 parts of polyester resin (A1-3), 30 parts of polyester resin (B1-1), 5.5 parts of jER157S70 (E-1) and 0.4 parts of 2-phenylimidazole (F-2) were mixed and fed to a twin-screw kneader at 80 kg / hour, and kneaded and extruded at 160°C and 90 rpm for 3 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-6). The glass transition temperature Tg of (C-6) was 1.0 g / h. C The temperature was 53.3°C, the acid value was 14.5 mg KOH / g, and the reaction rate was 96%.
[0166] <Example 7> [Production of toner binder (C-7)] 40 parts of polyester resin (A1-4), 60 parts of polyester resin (B1-2), 17.6 parts of jER1004 [bisphenol A type epoxy resin, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent 897, the same applies below] (E-3) and 0.2 parts of 2-ethyl-4-methylimidazole (F-3) were mixed and fed to a twin-screw kneader at 80 kg / hour, and kneaded and extruded at 150°C and 90 rpm for 15 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-7). The glass transition temperature Tg of (C-7) was 1.0 g / h. C The temperature was 54.5°C, the acid value was 6.7 mgKOH / g, and the reaction rate was 96%.
[0167] <Example 8> [Production of toner binder (C-8)] 50 parts of polyester resin (A1-1), 50 parts of crystalline vinyl resin (B2-1), 4.7 parts of jER157S70 (E-1) and 0.1 parts of imidazole (F-1) were mixed and fed to a twin-screw kneader at 80 kg / hr, and kneaded and extruded at 180°C and 90 rpm for 5 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain toner binder (C-8). The endothermic peak top temperature Tm of (C-8) was 58.1°C, and the glass transition temperature Tg C The temperature was 38.2°C, the acid value was 11.4 mg KOH / g, and the reaction rate was 96%.
[0168] <Example 9> [Production of toner binder (C-9)] 70 parts of polyester resin (A1-2), 30 parts of crystalline vinyl resin (B2-2), 5.1 parts of jER157S70 (E-1) and 0.2 parts of 2-phenylimidazole (F-2) were mixed and fed to a twin-screw kneader at 80 kg / hr, and kneaded and extruded at 180°C and 90 rpm for 5 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-9). The endothermic peak top temperature Tm of (C-9) was C is 46.2℃, glass transition temperature Tg C The temperature was 34.6°C, the acid value was 6.3 mgKOH / g, and the reaction rate was 96%.
[0169] <Example 10> [Production of toner binder (C-10)] 70 parts of polyester resin (A1-2), 30 parts of crystalline vinyl resin (B2-3), 5.1 parts of jER157S70 (E-1) and 0.2 parts of 2-ethyl-4-methylimidazole (F-3) were mixed and fed to a twin-screw kneader at 80 kg / hr, and kneaded and extruded at 180°C and 90 rpm for 5 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain toner binder (C-10). The endothermic peak top temperature Tm of (C-10) was C is 88.8℃, glass transition temperature Tg C The temperature was 34.8°C, the acid value was 6.4 mg KOH / g, and the reaction rate was 95%.
[0170] <Example 11> [Production of toner binder (C-11)] 50 parts of polyester resin (A1-3), 50 parts of crystalline vinyl resin (B2-4), 3.7 parts of EPPN-201 (E-2) and 0.2 parts of imidazole (F-1) were mixed and fed to a twin-screw kneader at 80 kg / hr, and kneaded and extruded at 150°C and 90 rpm for 2 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain toner binder (C-11). The endothermic peak top temperature Tm of (C-11) was C is 57.1℃, glass transition temperature Tg C The temperature was 50.8°C, the acid value was 10.4 mg KOH / g, and the reaction rate was 96%.
[0171] <Example 12> [Production of toner binder (C-12)] 40 parts of polyester resin (A1-2), 60 parts of crystalline vinyl resin (B2-5), 10.8 parts of jER1004 (E-3) and 0.1 parts of imidazole (F-1) were mixed and fed to a twin-screw kneader at 80 kg / hr, and kneaded and extruded at 160°C and 90 rpm for 6 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-12). The endothermic peak top temperature Tm of (C-12) was C is 59.2℃, glass transition temperature Tg CThe temperature was 34.2°C, the acid value was 4.4 mg KOH / g, and the reaction rate was 95%.
[0172] <Example 13> [Production of toner binder (C-13)] 30 parts of polyester resin (A1-4), 70 parts of crystalline vinyl resin (B2-1), 4.3 parts of jER157S70 (E-1) and 0.2 parts of 2-ethyl-4-methylimidazole (F-3) were mixed and fed to a twin-screw kneader at 80 kg / hr, and kneaded and extruded at 150°C and 90 rpm for 5 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain toner binder (C-13). The endothermic peak top temperature Tm of (C-13) was C is 59.3℃, glass transition temperature Tg C The temperature was 54.1°C, the acid value was 10.7 mgKOH / g, and the reaction rate was 95%.
[0173] <Example 14> [Production of toner binder (C-14)] In a reaction tank equipped with a stirrer, 70 parts of polyester resin (A1-4), 30 parts of polyester resin (B1-1), 5.5 parts of EPPN-201 (E-2) and 0.4 parts of imidazole (F-1) were charged, and the mixture was reacted at 104°C for 180 minutes while stirring. The mixture was then taken out and cooled to obtain toner binder (C-14). The glass transition temperature Tg C The temperature was 55.6°C, the acid value was 16.6 mg KOH / g, and the reaction rate was 91%.
[0174] <Example 15> [Production of toner binder (C-15)] 70 parts of polyester resin (A1-5), 30 parts of polyester resin (B1-1), 1.4 parts of EHPE-3150 [1,2-epoxy-4-(2-oxiranyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol, manufactured by Daicel Corporation, epoxy equivalent 174, the same applies below] (E-4) and 0.2 parts of imidazole (F-1) were mixed, fed to a twin-screw kneader at 80 kg / hour, and kneaded and extruded at 199°C and 90 rpm for 15 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-15). The glass transition temperature Tg of (C-15) was 1.0 g / h. C The temperature was 44.2°C, the acid value was 1.4 mgKOH / g, and the reaction rate was 92%.
[0175] <Example 16> [Production of toner binder (C-16)] 40 parts of polyester resin (A1-6), 60 parts of crystalline vinyl resin (B2-5), 2.1 parts of jER157S70 (E-1) and 0.2 parts of imidazole (F-1) were mixed and fed to a twin-screw kneader at 80 kg / hr, and kneaded and extruded at 185°C and 90 rpm for 16 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain toner binder (C-16). The endothermic peak top temperature Tm of (C-16) was C is 59.1℃, glass transition temperature Tg C The temperature was -34.6°C, the acid value was 2.2 mg KOH / g, and the reaction rate was 95%.
[0176] <Example 17> [Production of toner binder (C-17)] 70 parts of polyester resin (A1-7), 30 parts of polyester resin (B1-1), 6.5 parts of jER157S70 (E-1) and 0.2 parts of 2-phenylimidazole (F-2) were mixed and fed to a twin-screw kneader at 80 kg / hour, and kneaded and extruded at 150°C and 90 rpm for 3 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C-17). The glass transition temperature Tg of (C-17) was 1.0 g / h. C The temperature was 57.2°C, the acid value was 15.9 mg KOH / g, and the reaction rate was 95%.
[0177] <Comparative Example 1> [Production of Toner Binder (C'-1)] 50 parts of polyester resin (A1-2), 50 parts of polyester resin (B1'-1), 3.0 parts of jER157S70 (E-1) and 0.1 parts of 2-ethyl-4-methylimidazole (F-3) were mixed and fed to a twin-screw kneader at 80 kg / hour, and kneaded and extruded at 180°C and 90 rpm for 5 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain toner binder (C'-1). The glass transition temperature Tg of (C'-1) was C The temperature was 48.3°C, the acid value was 10.8 mg KOH / g, and the reaction rate was 96%.
[0178] <Comparative Example 2> [Production of Toner Binder (C'-2)] 50 parts of polyester resin (A1-1), 50 parts of polyester resin (B1-1), and 2.4 parts of jER157S70 (E-1) were mixed and fed to a twin-screw kneader at 80 kg / hour, and kneaded and extruded at 180°C and 90 rpm for 60 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain a toner binder (C'-2). The glass transition temperature Tg of (C'-2) was C The temperature was 49.7°C, the acid value was 17.9 mg KOH / g, and the reaction rate was 90%.
[0179] <Comparative Example 3> [Production of toner binder (C'-3)] 100 parts of polyester resin (B1-1), 2.4 parts of jER157S70 (E-1) and 0.1 parts of imidazole (F-1) were mixed and fed to a twin-screw kneader at 80 kg / hr, and kneaded and extruded at 180°C and 90 rpm for 60 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain toner binder (C'-3). The glass transition temperature Tg of (C'-3) was C The temperature was 61.0°C, the acid value was 0.2 mg KOH / g, and the reaction rate was 0%.
[0180] <Comparative Example 4> [Production of Toner Binder (C'-4)] 50 parts of polyester resin (A1-1), 50 parts of crystalline vinyl resin (B2-1) and 0.1 parts of imidazole (F-1) were mixed and fed to a twin-screw kneader at 80 kg / hr, and kneaded and extruded at 180°C and 90 rpm for 60 minutes to carry out a crosslinking reaction. The mixture was cooled to obtain toner binder (C'-4). The endothermic peak top temperature Tm of (C'-4) was C is 59.8℃, glass transition temperature Tg C The temperature was 38.8°C, the acid value was 24.1 mgKOH / g, and the reaction rate was 0%.
[0181] <Comparative Example 5> [Production of Toner Binder (C'-5)] In a reaction tank equipped with a stirrer, 70 parts of polyester resin (A1-4), 30 parts of polyester resin (B1-1), and 5.5 parts of EPPN-201 (E-2) were charged, and the mixture was reacted at 104°C for 180 minutes while stirring. The mixture was then taken out and cooled to obtain toner binder (C'-5). The glass transition temperature Tg C The temperature was 55.4°C, the acid value was 27.4 mg KOH / g, and the reaction rate was 20%.
[0182] Table 4 shows the compositions and physical properties of the toner binders (C) and (C′) obtained in Examples 1 to 17 and Comparative Examples 1 to 5.
[0183] [Table 4]
[0184] The reaction rate of the toner binder was calculated by the following formula. Response rate = (AV ini -AV C ) / (AV ini -AV fin ) × 100(%), AV ini =(AV A1 ×W A1 +AV B ×W B ) / W tot AVfin =[AV A1 ×W A1 +AV B ×W B -(56100 / E Q )×W E ] / W tot AV A1 : acid value of polyester resin (A1), AV C : acid value of the toner binder (C), W A1 : parts by weight of polyester resin (A1), W B : parts by weight of resin (B), W E : parts by weight of epoxy resin (E), W tot : Polyester resin (A1), resin (B), epoxy compound (E), catalyst (F) Total weight parts E Q : Epoxy equivalent of (E)
[0185] <Toner manufacturing> To 88 parts of the toner binder [the toner binder obtained in each Example and Comparative Example], 7 parts of the pigment carbon black [MA-100, manufactured by Mitsubishi Chemical Corporation], 3 parts of the release agent carnauba wax, and 1 part of the charge control agent [T-77, manufactured by Hodogaya Chemical Co., Ltd.] were added, and a toner was prepared by the following method. First, the mixture was premixed using a Henschel mixer [FM10B, Nippon Coke & Engineering Co., Ltd.], then mixed using a twin-screw mixer [PCM-30, Ikegai Co., Ltd.]. Then, the mixture was finely pulverized using a supersonic jet mill, Labojet [KJ-25, Kurimoto Iron Works Co., Ltd.], and classified using an elbow jet classifier [EJ-L-3(LABO) type, Matsubo Co., Ltd.] to obtain toner particles with a volume average particle size D50 of 7 μm. Next, 100 parts of the toner particles were mixed with 1 part of hydrophobic silica (Aerosil R972, manufactured by Nippon Aerosil Co., Ltd.) as a fluidizing agent in a sample mill to obtain a toner.
[0186] The compositions and evaluation results of the toners using the toner binders obtained in each of the Examples and Comparative Examples are shown in Table 5. In addition, in Table 5, the toners obtained using the toner binders (C-1) to (C-17) of Examples 1 to 17 are shown as (T-1) to (T-17), and the toners obtained using the toner binders (C'-1) to (C'-5) of Comparative Examples 1 to 5 are shown as (T'-1) to (T'-5), respectively.
[0187] [Table 5]
[0188] [Toner performance evaluation] The methods for evaluating the low temperature fixing property, hot offset resistance, heat resistance storage stability, charge retention rate (under low temperature and low humidity conditions and under high temperature and high humidity conditions), water resistance, image strength, odor and durability of the obtained toners (T-1) to (T-17) and (T'-1) to (T'-5) are described below, along with the criteria for evaluation.
[0189] <Low temperature fixability> Toner is applied on the paper at 1.0 mg / cm 2 The powder was applied evenly so that it would be evenly distributed. The method for applying the powder to the paper surface was to use a printer without a thermal fixing unit. The paper was passed through a soft roller at a fixing speed (circumferential speed of the heating roller) of 213 mm / sec, and at a heating roller temperature range of 90 to 200°C in 5°C increments. The fixed image was then visually inspected for the presence or absence of cold offset, and the temperature at which cold offset occurs (MFT) was measured. The lower the temperature at which cold offset occurs, the better the low-temperature fixing ability is. Under these evaluation conditions, it is generally preferable that the MFT is 120° C. or less.
[0190] <Hot offset resistance> Using the same method as described above for low-temperature fixability, the toner was placed on the paper and the paper was passed through a soft roller at a fixing speed (heating roller peripheral speed) of 213 mm / sec and at a heating roller temperature range of 90 to 200° C. in 5° C. increments. The fixed image was then visually inspected for the presence or absence of hot offset, and the temperature at which hot offset occurred was measured. The higher the temperature at which hot offset occurs, the better the hot offset resistance. In this evaluation condition, a temperature of 180° C. or higher is preferable.
[0191] <Heat-resistant storage stability> 1 g of toner and 0.01 g of Aerosil R8200 (manufactured by Evonik Japan Co., Ltd.) were mixed for 1 hour using a shaker. The mixture was placed in a sealed container and left to stand for 48 hours in an atmosphere with a temperature of 40°C and a humidity of 80%, and the cohesion was measured using a powder tester to evaluate the heat resistance storage stability. The lower the value in the cohesion test determined by the following method, the more excellent the heat-resistant storage stability. Under these evaluation conditions, a value of 5% or less is preferable. Equipment: POWDER TESTER model PT-X (manufactured by Hosokawa Micron) Sieve openings: 355μm, 250μm, 150μm Vibration width: 1mm Vibration duration: 30 seconds Operation method: Set the sieves on the vibration table of the powder tester in the following order: top 355μm, middle 250μm, bottom 150μm. Place 1g of toner on the top sieve and vibrate with a vibration amplitude of 1mm for 30 seconds. Measure the weight of toner remaining on each sieve. Cohesion: Calculated from the weight of toner used for measurement and the weight of toner remaining after sieving. Cohesion degree (%)=(U / N+M / N×3 / 5+L / N×1 / 5)×100 U: weight of top row, M: weight of middle row, L: weight of bottom row, N: weight of sample (1g)
[0192] <Charge retention rate (low temperature and low humidity conditions and high temperature and high humidity conditions)> (1) 1 g of toner and 0.01 g of Aerosil R8200 (manufactured by Evonik Japan Co., Ltd.) were mixed in a shaker for 1 hour. 0.5 g of this mixture and 20 g of ferrite carrier (F-150, manufactured by Powder Tech Co., Ltd.) were placed in a 50 mL glass bottle, and the bottle was conditioned at 23°C and 50% relative humidity for 8 hours (referred to as low temperature and low humidity conditions). Similarly, the bottle was conditioned at 50°C and 95% relative humidity for 24 hours (referred to as high temperature and high humidity conditions). (2) The mixture was stirred by friction at 50 rpm for 10 minutes and 60 minutes using a Turbulent Shaker Mixer, and the charge amount after each time was measured using a blow-off charge amount measuring device (manufactured by Kyocera Chemical Corporation). Using the obtained values, "charge amount after 60 minutes of friction / charge amount after 10 minutes of friction" was calculated, and this was taken as the charge stability index. A larger charge stability index indicates a more excellent charge retention rate. Under these evaluation conditions, a charge stability index of 0.8 or more is preferable.
[0193] <Water resistance> (1) 1 g of toner and 0.01 g of Aerosil R8200 (manufactured by Evonik Japan Co., Ltd.) were mixed for 1 hour in a shaker. 0.5 g of this mixture and 20 g of ferrite carrier (F-150, manufactured by Powder Tech Co., Ltd.) were placed in a 50 mL glass bottle, and this was conditioned at 50°C and a relative humidity of 95% for 24 hours. (2) The degree of blocking was visually determined, and the water resistance was evaluated according to the following criteria.
[0194] [Judgment criteria] ◯: No blocking occurred at all, and water resistance was excellent. △: Blocking occurred in some areas, but water resistance was excellent. ×: Blocking occurred throughout the entire surface, and water resistance was poor.
[0195] <Image Intensity> Among the images fixed in the above-mentioned low-temperature fixing property evaluation, the image with the lowest fixing temperature was subjected to a scratch hardness test in accordance with JIS K5600-5-4 (1999) by applying a load of 10 g from directly above a pencil fixed at a 45-degree angle using a manual scratching method, and the image strength was evaluated from the pencil hardness at which the image was not scratched. A higher pencil hardness means better image strength. Generally, HB or higher is preferred.
[0196] <Odor> 1.0 g of the toner was placed in a glass test tube with a lid (φ15 mm × 150 mm), sealed, and heated for 5 minutes at 210° C. After that, the lid was removed, and 10 monitors checked the odor and evaluated it according to the following criteria. [Judgment criteria] ○: 0 to 1 person answered that it smells bad △: 2-6 people answered that it smells bad ×: 7 or more people answered that it smells bad
[0197] <Durability> Using the toner as a two-component developer, continuous copies were made using a commercially available monochrome copier [AR5030, manufactured by Sharp Corporation], and durability was evaluated according to the following criteria.
[0198] [Judgment criteria] ⊚: No change in image quality or fogging occurred on the 10,000th copy. ○: Fog occurs on the 10,000th copy. △: Fog occurred on the 6,000th copy. ×: Fog occurs on the 2,000th copy.
[0199] As is clear from the evaluation results in Table 5, the toners (T-1) to (T-17) using the toner binders produced in the respective Examples all achieved excellent results in all performance evaluations. On the other hand, the toners (T'-1) to (T'-5) using the toner binders produced in the respective Comparative Examples were poor in some performance items. Specifically, Comparative Example 1 used a toner binder in which polyester resin (A1) was epoxy-crosslinked in polyester resin (B1) having an acid value, and the epoxy crosslinking reduced the low viscosity components, deteriorating the low temperature fixability. Comparative Example 2 was, catalyst Comparative Example 3 did not use polyester resin (A1), and the performance was poor in each of hot offset resistance, charge retention rate, water resistance, image strength, and durability. Comparative Example 4 did not use epoxy compound (E), and the performance was poor in each of hot offset resistance, heat resistance storage stability, charge retention rate, water resistance, image strength, and durability. Comparative Example 5 did not use polyester resin (A2), and the performance was poor in each of hot offset resistance, heat resistance storage stability, charge retention rate, water resistance, image strength, and durability. catalyst(F) was not used, and the performance was poor in each of hot offset resistance, heat resistance storage stability, charge retention rate, water resistance, image strength, and durability. [Industrial Applicability]
[0200] The toner binder of the present invention maintains low-temperature fixing property and hot offset resistance, while being excellent in heat-resistant storage stability, charge retention rate (particularly charge retention rate under high temperature and high humidity conditions), water resistance, image strength, odor and durability, and can be suitably used as a toner for developing electrostatic images for use in electrophotography, electrostatic recording, electrostatic printing, etc. Further, it is suitable for use as an additive for paints, an additive for adhesives, particles for electronic paper, and the like.
Claims
1. A method for producing a toner binder, comprising the step of reacting a polyester resin (A1) having an acid value of 1 mgKOH / g or more, measured by a method specified in JIS K0070, with an epoxy compound (E) in the presence of a resin (B) having an acid value of less than 1 mgKOH / g, measured by a method specified in JIS K0070, and a catalyst (F), wherein the resin (B) is a polyester resin (B1) and / or a vinyl resin (B2), the vinyl resin (B2) is a crystalline vinyl resin that is a polymer having, as its constituent monomer, a monomer (a) which is a (meth)acrylate having a chain hydrocarbon group and having 21 to 40 carbon atoms and / or a vinyl ester having a chain hydrocarbon group and having 21 to 40 carbon atoms, and the catalyst (F) is a compound represented by the following general formula (1): 【Chemistry 1】 [In general formula (1), R 1 ~R 3 are each independently a hydrogen atom, an alkyl group, or an aryl group.
2. 2. The method for producing a toner binder according to claim 1, wherein the reaction temperature of the polyester resin (A1) and the epoxy compound (E) is 100 to 200° C.
3. 3. The method for producing a toner binder according to claim 1 or 2, wherein the epoxy compound (E) is a polyfunctional epoxy compound having an epoxy equivalent of 170 to 900.
4. 4. The method for producing a toner binder according to claim 1, wherein the acid value of the polyester resin (A1) is 7.0 to 50.0 mgKOH / g.
5. 5. The method for producing a toner binder according to claim 1, wherein the polyester resin (A1) has a glass transition temperature of -35 to 55°C.
6. 6. The method for producing a toner binder according to claim 1, wherein a weight ratio of the polyester resin (A1) to the epoxy compound (E) [(A1):(E)] is from 65:35 to 98:2.
Citation Information
Patent Citations
Resin composition for impregnation
JP1995179732A
toner resin composition
JP1999513137A
Electrophotographic toner, electrophotographic developer and image forming method
JP2007193069A
Toner and two-component developer
JP2015135485A
Toner binder and toner
JP2017003985A